PREGNANCY WITH BILATERAL METASTATIC OVARIAN TUMOUR - Jabeen, Sadaqat; Nisar, Maleeha; Hussain, Nighat (Journal of Ayub Medical College Abbottabad, 2017)
Metastatic ovarian tumours are extremely rare. The commonest primary site is usually stomach and the metastasis from this site is termed as krukenberg tumour. It accounts for 1-2% of malignant ovarian tumours. We present a case of 14 weeks’ pregnancy with metastatic bilateral malignant ovarian tumour is presented. Diagnosis was made on ultrasound. Tumour markers were insignificant. Patient underwent staging laparotomy with total abdominal hysterectomy and bilateral salpingo oophorectomy and partial omentectomy. She also had haematemesis. Endoscopy revealed suspicious growth in stomach, but biopsy report excluded it. Case was handed over to the oncologist for further management. Keywords: Ovarian Tumour; Pregnancy; Metastatic Ovarian Tumour; Krukenberg Tumour